Cys34 Adductomes Differ between Patients with Chronic Lung or Heart Disease and Healthy Controls in Central London - Liu,S; Grigoryan,H; Edmands,WMB; Dagnino,S; Sinharay,R; Cullinan,P; Collins,P; Chung,KF; Barratt,B; Kelly,F; Vineis,P; Rappaport,SM (Environmental Science and Technology (Washington), 2018)
Oxidative stress generates reactive species that modify proteins, deplete antioxidant defenses, and contribute to chronic obstructive pulmonary disease (COPD) and ischemic heart disease (IHD). To determine whether protein modifications differ between COPD or IHD patients and healthy subjects, we performed untargeted analysis of adducts at the Cys34 locus of human serum albumin (HSA). Biospecimens were obtained from nonsmoking participants from London, U.K., including healthy subjects (n = 20) and patients with COPD (n = 20) or IHD (n = 10). Serum samples were digested with trypsin and analyzed by liquid chromatography-high resolution mass spectrometry. Effects of air pollution on adduct levels were also investigated based on estimated residential exposures to PM2.5, O3 and NO2. For the 39 adducts with sufficient data, levels were essentially identical in blood samples collected from the same subjects on two consecutive days, consistent with the 28 day residence time of HSA. Multivariate linear regression revealed 21 significant associations, mainly with the underlying diseases but also with air-pollution exposures (p-value < 0.05). Interestingly, most of the associations indicated that adduct levels decreased with the presence of disease or increased pollutant concentrations. Negative associations of COPD and IHD with the Cys34 disulfide of glutathione and two Cys34 sulfoxidations, were consistent with previous results from smoking and nonsmoking volunteers and nonsmoking women exposed to indoor combustion of coal and wood.